List of political prisoners in the USSR = spisok politzakliuchennykh SSSR - Liubarskii, Kronid Arkadevich. (Cahiers du Samizdat, 1982)
Continues in part: Bulletin d’information.Absorbed by: Vesti iz SSSR.